Effect Of Pre-Treatments On Colour And Quality Of Sun And Solar Tunnel-Dried Chilli (Capsicum Annum L.) Var. Kashmir Long-1 (Applied Biological Research, 2018)
A study was carried out to assess the effects of drying methods and chemical  pretreatments on product quality of chilli, Capsicum annum, (var. Kashmir  Long-1). Pretreated chilli was open sun-dried and solar tunnel dried upto  optimum moisture levels and assessed for various physicochemical changes.  The results revealed that among the pretreated samples, 2.5% potassium  carbonate + 1% ground nut oil + 0.1% gum acacia + 0.001% butylated  hydroxy anisol L-1for 15 min had highest ascorbic acid (41.08 mg 100 g-1),  capsaicin (1.077% db) and reducing sugar (0.617% db) contents; and lowest  moisture (9.85%) and non-enzymatic browning (0.123) values. All the  treatments significantly enhanced the L* (31.56), a* (25.23), b* (13.44), C*  (27.35), h* (27.6) and ΔE* (3.89) values in solar tunnel-dried samples.  However, in sun-dried samples lower ascorbic acid (39.98 mg 100 g-1),  capsaicin (0.939% db) and reducing sugar (0.591% db) contents and higher  moisture (10.43%), non-enzymatic browning (0.146), L* (30.52), a* (24.23),  b* (12.68), C* (28.59), h* (28.0), and ΔE* (3.86) values were observed. Drying  time of solar tunnel-dried samples was 48 h as compared to 72 h in case of  sun-dried samples. The most efficient drying method was solar tunnel drying  as it retained the nutritional properties and colour characteristics and  reduced the drying time.
Keywords: Ascorbic acid; browning; capsiacin; colour measurement; drying chilli